On site, not out of mind: the role of experiential learning in the political science doctoral program. - Marando, Vincent L.; Melchior, Mary Beth (PS: Political Science & Politics, 1997)
The writers discuss the role of experiential learning in the political science doctoral program. They argue that the idea that political scientist doctoral students have mastered the norms of liberal democratic citizenship and do not need to be trained for nonacademic employment disguises the value of experiential learning for the doctoral student. They stress the benefits of including an experiential element in political science Ph.D. programs by discussing what they learned while developing one such course, the Maryland Graduate Public Service Fellowship Program, which has provided a broad range of Ph.D. students with the chance to have structured learning experiences in state and local agencies.